ANALYSIS OF DETERMINANTS OF OBESITY AND OVERWEIGHT RISK FACTORS AMONG ADOLESCENTS IN CENTRAL JAVA PROVINCE BASED ON THE 2023 INDONESIAN HEALTH SURVEY DATA - Yayuk Fathonah (SOSIOEDUKASI, 2025)
Background: Overweight and obesity among adolescents have become a growing public health issue in Indonesia, contributing to the risk of non-communicable diseases in adulthood. Risky dietary behaviors and low physical activity levels are suspected to play a role in the increasing prevalence of obesity in the adolescent age group. Objective: This study aims to identify the risk factors associated with overweight and obesity in adolescents aged 11–18 years in Central Java Province. Methods: This study employs a cross-sectional design with a quantitative approach, utilizing secondary data from the 2023 Indonesian Health Survey (SKI). The study subjects were 4,439 adolescents aged 11–18 years who met the inclusion criteria. Nutritional status was determined based on the Body Mass Index for Age (BMI/A). Data analysis included univariate analysis, bivariate analysis using chi-square tests, and multivariate analysis using multiple logistic regression. Results: In the multivariate analysis, the consumption of soft drinks ≥1 time per day was identified as an independent determinant that increases the risk of overweight and obesity (aOR = 3.742; 95% CI: 1.440–9.723). Instant noodle consumption was found to be associated with overweight and obesity at certain levels of consumption. Educational level, consumption of sweet foods, sweet beverages, and fatty foods were associated in the bivariate analysis, but were not significant after controlling for other variables. Conclusion: Daily soft drink consumption is a major risk factor for overweight and obesity among adolescents in Central Java. Prevention of adolescent obesity requires a comprehensive approach, including improvements in dietary patterns, increased physical activity, as well as family support and public policy interventions.